Elimination of Ascorbic Acid After High‐Dose Infusion in Prostate Cancer Patients: A Pharmacokinetic Evaluation. (7th October 2014) - Nielsen, Torben K.; Højgaard, Martin; Andersen, Jon T.; Poulsen, Henrik E.; Lykkesfeldt, Jens; Mikines, Kári J.
Abstract Treatment with high‐dose intravenous (IV) ascorbic acid (AA) is used in complementary and alternative medicine for various conditions including cancer. Cytotoxicity to cancer cell lines has been observed with millimolar concentrations of AA. Little is known about the pharmacokinetics of high‐dose IV AA. The purpose of this study was to assess the basic kinetic variables in human beings over a relevant AA dosing interval for proper design of future clinical trials. Ten patients with metastatic prostate cancer were treated for 4 weeks with fixed AA doses of 5, 30 and 60 g. AA was measured consecutively in plasma and indicated first‐order elimination kinetics throughout the dosing range with supra‐physiological concentrations. The target dose of 60 g AA IV produced a peak plasma AA concentration of 20.3 mM. Elimination half‐life was 1.87 hr (mean, S.D. ± 0.40), volume of distribution 0.19 L/kg (S.D. ±0.05) and clearance rate 6.02 L/hr (100 mL/min). No differences in pharmacokinetic parameters were observed between weeks/doses. A relatively fast first‐order elimination with half‐life of about 2 hr makes it impossible to maintain AA concentrations in the potential cytotoxic range after infusion stop in prostate cancer patients with normal kidney function. We propose a regimen with a bolus loading followed by a maintenance infusion based on the calculated clearance.